Prevalence of Rape and Its Predictors among Female Students Attending Elementary Schools: In the Case of Kule Refugee Camp, Gambella, Southwest Ethiopia-A Cross-Sectional Study - Bhan Sudan Kong; Wubishet Gezimu; Ababo Demeke; Abdissa Duguma (Hindawi Limited, 2023)
Background. Tragically, rape victims keep their ailments a secret from the police and their family members or significant others out of concern for societal stigma. The prevalence and severity of rape are highest among minorities, including girls and children who live as refugees. The current study assessed the prevalence of rape and its predictors among female students attending elementary schools in the Kule refugee camp, Gambella, southwest Ethiopia. Methods. An institution-based cross-sectional study was conducted from May 15 to 25, 2022, using an interviewer-administered structured questionnaire. A total of 211 participants were selected using a simple random sampling technique. The collected data were entered into EpiData and then exported to SPSS version 23 for analysis. The descriptive statistics were presented using frequencies, means, and standard deviations. A binary logistic regression model was used to test the association between the outcome and explanatory variables. The multivariable analysis included variables with p values of less than 0.25. Finally, statistical significance was declared at a p value of less than 0.05. Results. A total of 210 participants were involved in this study, which has a 99.5% response rate. Of these, 73 (34.8%) were subjected to rape. Shockingly, the majority (79.5%) of those who experienced rape reported that their perpetrator did not use a condom. Smoking (AOR: 4.3; 95% CI: 1.61, 10.93), drinking alcohol (AOR: 3.2; 95% CI: 1.43, 7.03), and having a boyfriend (AOR: 2.81; 95% CI: 21, 4.05) were found to be factors associated with rape. Conclusion. This study found a high prevalence of rape in the study area. The study also identified that participants' behaviors, such as having a boyfriend, smoking, and drinking alcohol, predispose them to rape. Therefore, we recommend that the camp's administrative bodies and humanitarian service organizations strengthen the preventive measures against rape crime, including the reinforcement of solid laws against perpetrators.